GAMBARAN TINGKAT PENGETAHUAN DAN SIKAP TENTANG PENDIDIKAN SEKS REMAJA KELAS X DI SEKOLAH MENENGAH ATAS NEGERI 1 SLEMAN TAHUN 2015 - Sidan, Elda Swastiti; Sumarah, Sumarah; Arum, Dyah Noviawati Setya (Jurnal Kesehatan Ibu dan Anak, 2016)
Adolescent problems which today are very complex and worrying, as shown by the low knowledge of adolescents about sexeducation, young women and men aged 14-19 years who claimed to have a boyfriend had sexual intercourse beforemarriage respectively reached 34, 7% and 30.9%. Less of information and counseling on sexual education is one of theissues teens. The research objective was to determine the level of knowledge and attitudes about teenage sex educationclass X at SMA Negeri 1 Sleman Year 2015. The method used is descriptive with cross sectional approach. The entirepopulation of students of class X with the number 176 in SMA Negeri 1 Sleman. Data collected by questionnaire that havebeen tested for validity and reliability are then tabulated in the form of a frequency distribution. The result is a level ofknowledge about adolescent sex education good majority, as many as 90.34%, followed by the category of pretty much as9.66%, and no respondents with less category. Attitudes of respondents to the most adolescent sex education in the categoryis support as many as 52.27% and the rest is in the category do not support as many as 47.73%. The level of knowledge andattitudesabout teenage sex education in class XSMANegeri 1 Sleman be ineithercategory and support.